Chain management and marketing performance of the banana industry in Eritrea - Zereyesus, Yacob Abrehe (University of the Free State, 2006)
The current marketing of agricultural products in general, and of bananas in particular, poses special problems for Eritrean farmers. Poor climatic conditions coupled with crude and inefficient agricultural technologies render agricultural output sub-optimal. The major production problems include shortage of capital and scarcity of land; shortage of farming materials; spoilage of bananas during harvesting due to inappropriate harvesting techniques and facilities and lack of technical know how. In addition, the main marketing problems comprise transport problems to stores; general storage problems; lack of information and spoilage during transport. Taking the above into account it should be noted that current trends towards the increased globalization of markets, trade liberalization, advances in information technology, consumer preferences and improved logistics means that the competitiveness of fruit industries in various regions and countries, as affected by the performance of their supply chains, is becoming increasingly important and will be even more important in the future. Cognisance should also be taken of the fact that much confusion exists regarding the exact meaning of the term competitiveness. Comparative advantage and competitiveness are related, but are often mistakenly exchanged for one another. Comparative advantage explains how trade benefits nations through more efficient use of their resource base when trade is totally unrestricted. Competitive advantage defines trade patterns as they exist in the real world, including all the barriers to free trade ignored by comparative advantage (Worley, 1996). Vitally important is to take cognizance of the fact that the establishment of a competitive supply chain is a prerequisite for an industry’s competitiveness and success. Based on this analysis, this study proposes what should be done to achieve a workable SCM for the banana industry in Eritrea. In its broader sense, the proposed structure of the SCM involves the introduction of horizontal strategic alliances between existing banana producers and the marketing group and a vertical relationship along the supply chain. Given that bananas comprise a considerable portion of the international trade makes it significant to this study. Bananas are also symbolic of the wide range of injustices present in international trade today. The Lomé Convention, which placed certain Latin American banana exporting countries at a disadvantage, was the root cause of trade disputes, and the eventual replacement of this Convention will have an impact on the future banana export prospects of ACP countries. Eritrean producers, like those of other ACP countries, therefore have little time to adjust and become competitive against “dollar” bananas on the European market, which at this point enjoy a production cost and quality advantage
Dissertation (M.Sc.Agric. (Agricultural Economics))--University of the Free State, 2003
Keywords: Bananas -- Eritrea -- Marketing; Farm produce -- Eritrea -- Marketing; Export marketing -- Eritrea; Banana trade -- Eritrea